Customize sneaker for promoting brand (principle footwear) / Ahmad Harith Ibrahim - Ibrahim, Ahmad Harith (Faculty of Art and Design, 2015)
Athletic shoe is a generic name for the footwear primarily designed for sports or other forms of physical exercise, but in recent years has come to be used for casual everyday activities. Athletic shoes are also known as training shoes or trainers (British English), sandshoes, gym boots or joggers (Australian English and Geordie English in the UK), running shoes, runners or gutties (Canadian English, Australian English, and Hiberno-English), sneakers (North American English and New Zealand English), tennis shoes (North American English and Australian English), gym shoes, tennies, sports shoes, sneaks, tackies (South African English and Hiberno-English), rubber shoes (Philippine English) or canvers (Nigerian English).